2016
DOI: 10.3389/fneur.2016.00228
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial Infusion of Autologous Bone Marrow Mononuclear Stem Cells in Subacute Ischemic Stroke Patients

Abstract: IntroductionBased on many preclinical and small clinical trials, stem cells can help stroke patient with the possibility of replacing the cells and supporting the remaining cells. The aim of this study was to evaluate the safety and feasibility of bone marrow mononuclear (BMMN) stem cell transplantation in subacute ischemic stroke patients.Materials and methodsThirty-nine (n = 39) patients with subacute ischemic cerebral infarct due to large artery occlusion in the middle cerebral artery (MCA) territory were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 28 publications
3
39
0
2
Order By: Relevance
“…The IA route has already been validated in a large animal model and transplantation of even large MSCs was safe and therapeutic in a canine ischemia model (Chung et al, 2009). There were also no adverse events as a result of IA delivery of bone marrow mononuclear cells in subacute ischemic stroke patients (Ghali, Yousef, Ragab, & ElZamarany, 2016).…”
Section: Intra-arterial Routementioning
confidence: 89%
See 1 more Smart Citation
“…The IA route has already been validated in a large animal model and transplantation of even large MSCs was safe and therapeutic in a canine ischemia model (Chung et al, 2009). There were also no adverse events as a result of IA delivery of bone marrow mononuclear cells in subacute ischemic stroke patients (Ghali, Yousef, Ragab, & ElZamarany, 2016).…”
Section: Intra-arterial Routementioning
confidence: 89%
“…The IA route has already been validated in a large animal model and transplantation of even large MSCs was safe and therapeutic in a canine ischemia model (Chung et al 2009). There were also no adverse events as a result of IA delivery of bone marrow mononuclear cells in subacute ischemic stroke patients (Ghali et al 2016). However, the effective diapedesis in diseases without or with little neuroinflammatory component, such as dysmyelination and related neurodegenerative disorders, is still unresolved and thus, this route of delivery also may have its limitations.…”
Section: Cell Delivery Routes Optimal For Wide Distribution Of Gpsmentioning
confidence: 99%
“…Cell transplantation after a week for up to 6 months is considered to be sub-acute treatment [ 2 , 3 , 5 , 8 , 11 , 13 , 14 , 15 , 17 , 20 , 22 , 24 , 26 , 27 , 28 , 34 , 36 , 42 ]. In addition to BMMNCs, autologous BMSCs are used for ex-vivo expansion within a time frame of approximately 1 month.…”
Section: Key Aspects Of Clinical Trialsmentioning
confidence: 99%
“…Lately, stem cell therapy has been recognized as a promising strategy that functionally enhances recovery from ischemic stroke. Thus, a variety of cells, including bone marrow mononuclear cells (BMMNCs) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], bone marrow/adipose-derived stem/stromal cells (BMSCs/ADMSCs) [ 4 , 6 , 7 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], umbilical cord blood cells (UCBCs) and hematopoietic stem cells [ 32 , 33 , 34 , 35 , 36 , 37 ], neural stem cells (NSCs) [ 34 , 36 , 38 , 39 , 40 , 41 , 42 , 43 ], olfactory ensheathing cells (OECs) [ 38 ], and fetal porcine cells [ 44 ], have been explored as candidate donors. Animal studies have indicated that such cells may ameliorate the neurological deficits that follow cerebral stroke, and some have been tested in clinical trials with somewhat favorable results.…”
Section: Introductionmentioning
confidence: 99%
“…5,37,38 The current advances in recanalization approaches may lead to increasing numbers of patients receiving cell therapy immediately after recanalization in the future, warranting the use of a transient stroke model for preclinical evaluation regardless of the targeted time point of cell administration, and would allow cell transplantation in a more acute stage after stroke onset in clinical trials. However, only a limited number of patients experience prompt recanalization, thus the permanent occlusion models might better reflect the presentday clinical situation except for intra-arterial cell transplantation.…”
Section: Cerebral Vessel Occlusion Modalitiesmentioning
confidence: 99%